The Association Between Preoperative Inspiratory Muscle Training Variables and Postoperative Pulmonary Complications in Subjects With Esophageal Cancer. - Overbeek, Meike C.; Reijneveld, Elja AE; Valkenet, Karin; van Adrichem, Edwin J.; Dronkers, Jaap J.; Ruurda, Jelle P.; Veenhof, Cindy (Respiratory Care, 2024)
BACKGROUND: Preoperative inspiratory muscle training (IMT) is frequently used in patients waiting for major surgery to improve respiratory muscle function and to reduce the risk of postoperative pulmonary complications (PPCs). Currently, the mechanism of action of IMT in reducing PPCs is still unclear. Therefore, we investigated the associations between preoperative IMT variables and the occurrence of PPCs in patients with esophageal cancer. METHODS: A multi-center cohort study was conducted in subjects scheduled for esophagectomy, who followed IMT as part of a prehabilitation program. IMT variables included maximum inspiratory pressure (PImax) before and after IMT and IMT intensity variables including training load, frequency, and duration. Associations between PImax and IMT intensity variables and PPCs were analyzed using independent samples t tests and logistic regression analyses, corrected for age and pulmonary comorbidities and stratified for the occurrence of anastomotic leakages. RESULTS: Eighty-seven subjects were included (69 males; mean age 66.7 6 7.3 y). A higher PImax (odds ratio 1.016, P 5 .07) or increase in PImax during IMT (odds ratio 1.020, P 5 .066) was not associated with a reduced risk of PPCs after esophagectomy. Intensity variables of IMT were also not associated (P ranging from .16 to .95) with PPCs after esophagectomy. Analyses stratified for the occurrence of anastomotic leakages showed no associations between IMT variables and PPCs. CONCLUSIONS: This study shows that an improvement in preoperative inspiratory muscle strength during IMT and training intensity of IMT were not associated with a reduced risk on PPCs after esophagectomy. Further research is needed to investigate other possible factors explaining the mechanism of action of preoperative IMT in patients undergoing major surgery, such as the awareness of patients related to respiratory muscle function and a diaphragmatic breathing pattern.